The Dynamics of Capital Adequacy, Credit Risk, and Liquidity in Optimizing the Profitability of BUMN Banks in Indonesia - Olivia, Monica; Wulan Wahyu Ningrum (Future Science, 2024)
This study evaluates the effect of Capital Adequacy, Credit Risk, and Liquidity on the profitability of state-owned banks registered with OJK during the period 2015-2023. The purposive sampling technique was used to select four banks that fit the research criteria. The data was processed using multiple linear regression analysis using EViews 10 software. Based on partial analysis (T-test) shows that Capital Adequacy Ratio (CAR) has no significant effect on Return on Assets (ROA), while Non-Performing Loan (NPL) has a significant negative effect on ROA, and Loan Deposit Ratio (LDR) has a significant positive effect on ROA. Simultaneously (F test), CAR, NPL, and LDR collectively have a significant effect on the profitability of State-Owned Commercial Banks in Indonesia.